Ending the physical punishment of children: a guide for clinicians and practitioners - Gershoff, Elizabeth T.; Lee, Shawna J. (American Psychological Association, 2020)
Brief Online Education / George W. Holden & Alan S. Brown -- Alternative Biblical Interpretations Intervention / Cindy Miller-Perrin & Robin Perrin -- Baby Books / Stephanie M. Reich & Guadalupe Díaz -- Motivational Interviewing / George W. Holden & Grant W. O. Holland -- Play Nicely / Seth Scholer -- A Safe Environment for Every Kid (SEEK) / Howard Dubowitz -- The Video Interaction Project (VIP) / Caitlin Canfield, Erin Roby, & Alan Mendelsohn -- An Educational Intervention for Health Care Providers / Gail Hornor, Saribel Garcia Quinones, Deborah Bretl, Ellen Chiocca, Carrie Donnell, Katharine Doughty, Bridget Marshall, & Kristen Morris -- Positive Discipline in Every Day Parenting (PDEP) / Joan E. Durrant -- The ACT Raising Safe Kids Program / Michele Knox & Morgan Dynes -- The Chicago Parent Program / Susan M. Breitenstein, Deborah Gross, & Amie F. Bettencourt -- The Moms' Empowerment Program / Andrew Grogan-Kaylor, Kathryn H. Howell, Maria M. Galano, & Sandra A. Graham-Bermann -- Triple P--Positive Parenting Program / Ronald J. Prinz -- No Hit Zones / Elizabeth T. Gershoff -- Legal Prohibitions on Physical Punishment / Elizabeth T. Gershoff & Joan E. Durrant.